Induction of resilience strategies against biochemical deteriorations prompted by severe cadmium stress in sunflower plant when Trichoderma and bacterial inoculation were used as biofertilizers - Abeed, Amany H. A.; Mahdy, Rasha E.; Alshehri, Dikhnah; Hammami, Inès; Eissa, Mamdouh A.; Abdel Latef, Arafat Abdel Hamed; Mahmoud, Ghada Abd-Elmonsef (Frontiers in Plant Science, 2022)
Background: Utilization of agriculturally significant microorganisms as biofertilizers in mitigating the impact of stressors on plant growth and development has constantly been arising as eco-friendly practices. A greenhouse experiment was performed using Trichoderma harzianum and plant growth-promoting bacteria (Azotobacter chroococcum and Bacillus subtilis) individually and integrally to explore their potentiality in underpinning various resilience mechanisms versus various cadmium (Cd) levels (0, 50, 100, and 150 mg /kg soil). Microorganisms were analyzed for cadmium tolerance and biosorption capacity, indoleacetic acid production, and phosphate and potassium solubilization in vitro. Plant growth parameters, water relations, physiological and biochemical analysis, stress markers and membrane damage traits, and nutritional composition were estimated. Results: Unequivocal inversion from a state of down-regulation to upregulation was distinct under microbial inoculations on plant fresh and dry weights, height, leaf-specific area, chlorophylls, net assimilation rate, nitrogen and carbon metabolism, relative water content, stomatal conductance, respiration rate, water use efficiency; some metabolites such as phenolics, flavonoids, and proline; antioxidants including phytochelatins, ascorbic acid, and reduced glutathione; enzymes activity including ascorbate peroxidase, glutathione peroxidase, guaiacol peroxidase, phenylalanine ammonia-lyase, and glutathione-S-transferase; nutritional profile including nitrate and phosphorus. Whereas a hampering effect mediated by microbe inoculation was registered on levels of superoxide anion, hydroxyl radical and hydrogen peroxide, malondialdehyde, electrolyte leakage, lipoxygenase, and polyphenol oxidase activities, and available soil and plant cadmium concentrations. Conclusions: However, strategies of microbes-induced resilience are largely exclusive and divergent. Biofertilizing potential of T. harzianum showed that Cd was employed as a beneficial element while using Azotobacter chroococcum and Bacillus subtilis manifested bioprotection potential by neutralizing the potential side-effects from Cd toxicity. The synergistic use of fungi and bacteria proved the highest efficiency in imparting sunflower adaptability under cadmium stress.